2019
DOI: 10.4274/tjps.galenos.2018.59023
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Antibiofilm Activities of Ceragenins against <i>Pseudomonas aeruginosa</i> Clinical Isolates

Abstract: Pseudomonas aeruginosa, antibiyotiklere oldukça dirençli ve biyofilm oluşturma yeteneği nedeniyle hayatı tehdit eden enfeksiyonlara neden olabilmektedir. Antimikrobiyal peptidlerin aktivitelerini taklit eden cerageninler, P. aeruginosa'ya karşı da güçlü etki gösteren yeni umut verici ajanlardır. Çalışmamızın amacı, cerageninlerin P. aeruginosa suşlarına karşı antibakteriyel ve antibiyofilm aktivitelerini değerlendirerek, kolistin ve siprofloksasinle karşılaştırmaktır. Gereç ve Yöntemler: Yirmi beş P. aeruginos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Biofilm is also an important factor in S. maltophilia infections, [48] and the anti-biofilm effects of ceragenins suggest that they have the potential for application against S. maltophilia strains [19,49]. The high anti-biofilm activity of ceragenins is confirmed by many previous studies [50][51][52]. For example, Chmielewska et al demonstrated the effective action of CSA-13, CSA-44 and CSA-131 against biofilm produced by the NDM-1 (New Delhi metallo-β-lactamase-1) producing strains Escherichia coli BAA-2471, Enterobacter cloacae BAA-2468, and Klebsiella pneumoniae BAA-2472 I BAA-2473 [53].…”
Section: Discussionsupporting
confidence: 52%
“…Biofilm is also an important factor in S. maltophilia infections, [48] and the anti-biofilm effects of ceragenins suggest that they have the potential for application against S. maltophilia strains [19,49]. The high anti-biofilm activity of ceragenins is confirmed by many previous studies [50][51][52]. For example, Chmielewska et al demonstrated the effective action of CSA-13, CSA-44 and CSA-131 against biofilm produced by the NDM-1 (New Delhi metallo-β-lactamase-1) producing strains Escherichia coli BAA-2471, Enterobacter cloacae BAA-2468, and Klebsiella pneumoniae BAA-2472 I BAA-2473 [53].…”
Section: Discussionsupporting
confidence: 52%
“…As ceragenins have been described to disrupt fungal membranes, this was investigated as a potential mode of action of DOCA-NH 2 . 8,11,31…”
Section: Resultsmentioning
confidence: 99%
“…Even though CSA-13 shows better activity than CSA-142 and CSA-192, second-generation ceragenins might be more beneficial than the first-generation due to better stability, environmentally friendly, and easier preparation [ 144 ]. Another second-generation ceragenins—CSA-131—exhibited bactericidal and excellent antibiofilm properties against P. aeruginosa [ 145 ] and S. maltophilia [ 146 ] as well as a synergistic activity when combined with colistin against CRAB [ 147 ].…”
Section: Newly Prospective Pharmaceutical Candidates To Mitigate Antimicrobial Resistancementioning
confidence: 99%